2022
DOI: 10.21043/equilibrium.v10i2.15730
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure: Analysis of the Islamic Banking Industry in the ASEAN Region

Abstract: <p><em>This study aims to evaluate the factors that influence the capital structure of the Islamic banking industry in the ASEAN region using the trade-off theory as a basis for decision-making. In trade-off theory, book leverage can proxy capital structure as the dependent variable and bank-specific factors, including profitability, earnings volatility, bank size, asset growth, asset structure, and bank age, as independent variables. In addition, it also considers macroeconomic conditions, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…The results showed a positive impact of profitability on book leverage, and the descriptive statistics showed that ROA is close to 1.56%. This result supports the trade-off theory and Signaling Theory in the fact that highly profitable banks can increase the amount of debt to reduce taxes (Waluyani & Muflih, 2022). In other words, the increase in profit will provide a positive signal to shareholders about the financial affairs of the future of the bank for investors.…”
Section: Regression Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The results showed a positive impact of profitability on book leverage, and the descriptive statistics showed that ROA is close to 1.56%. This result supports the trade-off theory and Signaling Theory in the fact that highly profitable banks can increase the amount of debt to reduce taxes (Waluyani & Muflih, 2022). In other words, the increase in profit will provide a positive signal to shareholders about the financial affairs of the future of the bank for investors.…”
Section: Regression Resultssupporting
confidence: 83%
“…Anggareni et al (2021) and Fauziah et al (2020) showed a positive impact of Return on Assets (ROA) on the capital structure of Islamic banks. These results support the trade-off theory, in which highly profitable banks increase the amount of debt to reduce taxes (Waluyani & Muflih, 2022). In contrast, the pecking order theory predicts a negative impact of profitability on capital structure, so banks start using internal sources to finance their assets, then they use debt to finance their assets (Guizani, 2021;Sheikh & Qureshi, 2017;Saif-Alyousfi et al, 2020).…”
Section: Empirical Studies On Determinants Of Capital Structuresupporting
confidence: 68%
See 3 more Smart Citations